Differences in the Efficiency of the Vertical Transfer of Windblown Sediment over Different Ploughed Surfaces during Wind Erosion Events - Mohamed Taieb Labiadh; Gilles Bergametti; Jean Louis Rajot; Christel Bouet; Mohsen Ltifi; Saâd Sekrafi; Thierry Henry des Tureaux (Land, 2021)
Airborne sediment fluxes were measured in southern Tunisia on two experimental plots tilled with a moldboard and a tiller plough, respectively, during five wind erosion events of different intensities. The sediment fluxes were sampled on both plots using a mast equipped with seven sand traps positioned between ≈10 and 120 cm height. The windblown sediment fluxes in the 0–100 cm layer were about eight times higher on the plot tilled using the tiller plough compared to the plot tilled using the moldboard plough due to different efficiencies in the trapping of the saltating particles in the furrow, depending on the ridges characteristics. On both plots, sediment fluxes of larger particles were depleted in the sediment samplers compared to the proportions measured in the soil from which they were derived. When examining the sediment flux in the 30–100 cm layer, we observed that the efficiency of the vertical transfer was about twice higher on the moldboard plot than on the tiller one. This implies that a higher fraction of the sediment mobilized by wind can be transported over long distances in the case of a surface ploughed with a moldboard. This result could reduce in part the benefit of using the moldboard instead of the tiller plough regarding soil loss by wind erosion.